2020
DOI: 10.1071/cp19387
|View full text |Cite
|
Sign up to set email alerts
|

Linkage mapping and whole-genome predictions in canola (Brassica napus) subjected to differing temperature treatments

Abstract: Canola (Brassica napus L.) is grown on >8 Mha in Canada and is sensitive to high temperatures; therefore, research on breeding methodologies to improve heat-stress tolerance is warranted. This study utilised a doubled-haploid population created from two parents (PB36 and PB56) that differed in their ability to set seed following growth at high temperatures. The experiment was designed to identify potential quantitative trait loci (QTLs) responsible for conferring tolerance to increased temperatures, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…The inclusion of genotype-by-environment interaction in the GBLUP model resulted in further, though slight, improvements in predictions. Koscielny et al ( 2020 ) confirmed these findings, demonstrating higher accuracy in whole-genome predictions within the stress treatment than within the control treatment for the majority of traits evaluated. It is therefore important, even in the genomics era, to link selected phenotypic or demographic models with the underlying processes of genomic variation.…”
Section: Genomic Selection In Crop Improvementmentioning
confidence: 76%
“…The inclusion of genotype-by-environment interaction in the GBLUP model resulted in further, though slight, improvements in predictions. Koscielny et al ( 2020 ) confirmed these findings, demonstrating higher accuracy in whole-genome predictions within the stress treatment than within the control treatment for the majority of traits evaluated. It is therefore important, even in the genomics era, to link selected phenotypic or demographic models with the underlying processes of genomic variation.…”
Section: Genomic Selection In Crop Improvementmentioning
confidence: 76%
“…Even a short period of high temperature stress at flowering can have a negative impact on seed quality parameters. However, the heat sensitivity of canola has been reported at 29.5 °C, 30 °C, 35 °C, and 31 °C 24 26 . These studies have reported a yield loss in canola due to high temperature stress at sensitive crop stages causing a decrease of 15–20% 27 , 55% 26 , and 38% 1 .…”
Section: Introductionmentioning
confidence: 99%
“…However, the heat sensitivity of canola has been reported at 29.5 °C, 30 °C, 35 °C, and 31 °C 24 26 . These studies have reported a yield loss in canola due to high temperature stress at sensitive crop stages causing a decrease of 15–20% 27 , 55% 26 , and 38% 1 . High temperature stress generally affects the quantity and quality of canola 28 .…”
Section: Introductionmentioning
confidence: 99%